1988
DOI: 10.1038/jcbfm.1988.10
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vascular and Metabolic Reactivity as Indices of Ischaemia in the Penumbra

Abstract: The reactivities of cerebral cortical blood flow (hydrogen clearance) and of compensated NADH fluorescence to local cortical electrical stimulation were examined on the marginal gyrus before and after transorbital occlusion of the middle cerebral artery in cats. Prestimulus cerebral blood flow (CBF) was 38.2 ± 12.9 (SD) ml 100 g−1 min−1 and fell to 19.8 ± 11.1 following occlusion (p < 0.02). Peak hydrogen clearance rate (percent increase above prestimulus clearance) was 81.6 ± 53.6 and fell to 19.9 ± 29.8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Numerous reports confirmed that neuronal excitation in intact brain was accompanied by sustained oxidation of NADH [19,30,[34][35][36][37][38][39][40][41][42][43][44][45]. A close correlation was also observed between NADH oxidation and oxygen consumption in cat and rat neocortex [46,47].…”
Section: Redox Responses In Excited Brain Tissue In Vivosupporting
confidence: 50%
“…Numerous reports confirmed that neuronal excitation in intact brain was accompanied by sustained oxidation of NADH [19,30,[34][35][36][37][38][39][40][41][42][43][44][45]. A close correlation was also observed between NADH oxidation and oxygen consumption in cat and rat neocortex [46,47].…”
Section: Redox Responses In Excited Brain Tissue In Vivosupporting
confidence: 50%
“…The demonstration of impaired vasoreactivity to cortical stimulation in the penumbra [28] and the knowledge that spreading depression is associated with movement of extracellular calcium into cells suggest that cytotoxicity might arise from abnormally sustained increases in cytosolic calcium. Gido and colleagues [29], however, were unable to confirm this.…”
Section: How Do Peri-infarct Depolarizations Increase Lesion Size?mentioning
confidence: 98%
“…Since total blood flow in the MCA territory is limited by the diameter of anatomoses, 25 any focal increase in blood flow in this territory is likely to be accompanied by a decrease in perfusion in other parts of the same arterial territory. Strong et al 26 showed that stimulation of a cortical area within the MCA territory after MCAO caused an increase in blood flow in the stimulated area, with a decrease in blood flow in an adjacent region. It is difficult to assess the clinical relevance of the brief enhancement of ischemic conditions by PIDs in the penumbra, since the occurrence of PIDs in humans has not been studied during stroke.…”
Section: Discussionmentioning
confidence: 99%